Aggressive approach for spontaneous pneumothorax treatment in children with Marfan syndrome? - Zarfati, Angelo; Frediani, Simone; Pardi, Valerio; Aloi, Ivan Pietro; Madafferi, Silvia; Accinni, Antonella; Bertocchini, Arianna; Inserra, Alessandro (Frontiers in Pediatrics, 2023)
This study analyzes our experience with the management of the first episode of spontaneous pneumothorax in children and adolescents with Marfan syndrome WHAT'S KNOWN ON THIS SUBJECT: There is a scarcity of pediatric literature on management, and no specific guidelines exist. Our aim was to analyze the management of spontaneous pneumothorax in children and adolescents with Marfan syndrome, comparing syndromic and nonsyndromic patients.WHAT THIS STUDY ADDS: Treatment failure, contralateral occurrence, ipsilateral recurrence, and the need for surgery/chest drain during follow-up make management of patients with Marfan syndrome and spontaneous pneumothorax more difficult. In patients with a diagnosed MS a more aggressive first-line management should be considered.